Effect of interface property on hydraulic fracture vertical propagation behavior in layered formation based on discrete element modeling. (9th May 2018) - Tan, Peng; Jin, Yan; Xiong, Zhenyu; Mian, Chen; Hou, Bing
Abstract: Prediction of fracture vertical propagation geometry is a tremendous challenge and of great importance in the process of hydraulic fracturing. Based on a discrete element method, a 2D fluid–solid coupling model is established with a particle flow code for simulating hydraulic fracture initiation and vertical propagation. The effects of in situ stress and the interface property (including the cementing strength and the angle of the layer interface) on fracture propagation behavior are discussed. The results indicate that hydraulic fractures tend to cross the layer interface under the conditions of a high in situ stress difference (Δ σ ) and a high angle of layer interface (Δ θ ) between the direction of the layer interface and the vertical in situ stress. The cementing strength of the layer interface can also affect the fracture vertical propagation behavior as well as the stress difference Δ σ and the angle Δ θ . The greater the cementing strength, the smaller the stress difference and interface angle required to penetrate the layer interface. When the tensile strength ratio ( R 0 ) of the layer interface to the average value of the upper and lower layers is less than 0.3, under the condition of Δ θ = 45°, hydraulic fracture cannot cross the interface no matter how great the stress difference. A comparison between numerical modeling and experimental investigation results indicates that there is a good correlation with the fracture crossing behavior.